Harnessing in situ glutathione for effective ROS generation and tumor suppression via nanohybrid-mediated catabolism dynamic therapy. (February 2022) - Peng, Si-Yuan; Liu, Xin-Hua; Chen, Qi-Wen; Yu, Yun-Jian; Liu, Miao-Deng; Zhang, Xian-Zheng
Abstract: The overexpression of glutathione (GSH) in cancer cells has long been regarded as the primary obstacle for reactive oxygen species (ROS)-involved anti-tumor therapies. To solve this issue, a ferric ion and selenite-codoped calcium phosphate (Fe/Se–CaP) nanohybrid here is fabricated to catabolize endogenous GSH, instead of directly deleting it, to trigger a ROS storm for tumor suppression. The selenite component in Fe/Se–CaP can catabolize GSH to superoxide anion (O2 − ) and hydroxyl radicals (OH) via cascade catalytic reactions, elevating oxidative stress while destroying antioxidant system. The doped Fe can further catalyze the soaring hydrogen peroxide (H2 O2 ) originated from O2 − to OH via Fenton reactions. Collectively, Fe/Se–CaP mediated self-augmented catabolism dynamic therapy finally induces apoptosis of cancer cells owing to the significant rise of ROS and, combined with CaP adjuvant, evokes adaptive immune responses to suppress tumor progression, providing an innovative train of thought for ROS-involved anti-tumor therapies. Graphical abstract: Image 1